ANALISIS PARAMETER SUMBER SPEKTRAL GEMPABUMI VTA (VULKANO TEKTONIK-A) TERHADAP AKTIVITAS VULKANIK GUNUNG SINABUNG - Tri Kusmita; Kirbani Brotopuspito; Hetty Triastuty (Prodi Fisika FST UNJA, 2019)
The source parameters describe the different physical properties of seismic volumes under the volcanoes. Source parameters that can be used to distinguish seismic events that are generated by different types of volcanoes activities. Temporary changes of the spectral source parameters provided a description of the main events during the eruption process. Source parameters are calculated by correlating the relationship between source frequency at spectral displacement (corner frequency) and source parameters based on spectral sources of the Brune model (1970). The angular frequency obtained by applying the FFT algorithm to the VTA spectral displacement. The source parameters analyzed from this VTA earthquake are the spectral slope, seismic moment, stress drop, length of rupture, moment magnitude and radiation energy. Based on the obtained corner frequency (12 Hz-13 Hz), seismic moment, moment magnitude and energy radiation respectively were at 0.2 -1.9 x 1012 Nm, 0.7 - 2 Mw, and 0.1 - 9.5 x 1015 erg. The length of rupture were from 144.2 to 243.1 m, the spectra slope has 2.1 - 7.8 dB/cm, and stress drop are 0.1 - 7,6 bar. From the results of this study, it can be concluded that the changes of spectra characteristic and fluctuate of source patrameters value of VTA earthquakes was asosiated with the different volcanic activity of Sinabung. Keywords: spectral, VTA, source parameter, volcanic earthquake